Acute kidney injury in pediatric patients with rhabdomyolysis - Young Shin Lim; Heeyeon Cho; Sang Taek Lee; Yeonhee Lee (Korean Pediatric Society, 2018)
PurposeThis study aimed to evaluate the clinical findings in pediatric rhabdomyolysis and the predictive factors for acute kidney injury (AKI) in Korean children.MethodsMedical records of 39 Korean children, who were newly diagnosed with rhabdomyolysis from January 2008 to December 2015, were retrospectively analyzed. The diagnosis was made from the medical history, elevated serum creatinine kinase level >1,000 IU/L, and plasma myoglobin level >150 ng/mL. Patients with muscular dystrophy and myocardial infarction were excluded.ResultsThe median patient age at diagnosis was 14.0 years (range, 3-18 years), and the male to female ratio was 2.5. The most common presenting symptom was myalgia (n=25, 64.1%), and 14 patients (35.9%) had rhabdomyolysis-induced AKI. Eighteen patients (46.2%) had underlying diseases, such as epilepsy and psychotic disorders. Ten of these patients showed rhabdomyolysis-induced AKI. The common causes of rhabdomyolysis were infection (n=12, 30.7%), exercise (n=9, 23.1%), and trauma (n=8, 20.5%). There was no difference in the distribution of etiology between AKI and non-AKI groups. Five patients in the AKI group showed complete recovery of renal function after stopping renal replacement therapy. The median length of hospitalization was 7.0 days, and no mortality was reported. Compared with the non-AKI group, the AKI group showed higher levels of peak creatinine kinase and myoglobin, without statistical significance.ConclusionThe clinical characteristics of pediatric rhabdomyolysis differ from those observed in adult patients. Children with underlying diseases are more vulnerable to rhabdomyolysis-induced AKI. AKI more likely develops in the presence of a high degree of albuminuria.